Diversity and traditional uses of Zingiberaceae in Nakhon Phanom province, Thailand - Saensouk, Surapon; Saensouk, Piyaporn; Pasorn, Pattana; Chanshotikul, Nachayut (Food Agricultural Sciences and Technology, 2018)
The objective of this study was to determine the diversity, ecology, conservation status and traditional uses of three tribes, 12 genera and 57 species of Zingiberaceae that were identified during a botanical survey between January and December 2016 in Nakhon Phanom province, Thailand. Curcuma, Globba and Zingiber are the most diverse genera with nine each. Alpinia and Kaempferia are the second most diverse genera with eight species each. While the genera Hedychium and Etlingera are the least diverse with one species each. Scientific name, vernacular name, flowering and fruiting periods, ecological and distribution data, conservation status of each species and ecological and morphology-based key to the species are provided. Four species are reported as endemic to Thailand. Eighteen species are recorded as rare species. It was revealed that the traditional uses of Zingiberaceae species in Nakhon Phanom province were most frequency for medicine, food (including spices), ornamental plants and rituals. Rhizomes, roots, pseudostem, inflorescences, leaves and fruits are the parts of the plant used. This study is the first report from Nakhon Phanom province.